GNSS remote sensing of the environment - Awange, Joseph (2018)
© Springer International Publishing AG 2018. GNSS satellites such as GPS are playing an increasingly crucial role in tracking low earth orbiting (LEO) remote sensing satellites at altitudes below 3000 km with accuracies of better than 10 cm [2].